Self-Reflective Practice on Scaffolding Skills: A Self-Study during the Student-Teacher's Online Teaching Practicum Process - Aulia Adilla Aji; Yazid Basthomi; Mirjam Anugerahwati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: This study aims to self-reflect the student-teacher’s (ST’s) scaffolding during her online teaching practicum practice. The self-reflective was conducted in six meetings using a Zoom Application. It utilized a thematic analysis from Braun Clarke (2006). The findings showed that the student-teacher was able to: (1) be aware of her scaffolding drawbacks and improved significantly in the next meetings, (2) improve students’ understanding, (3) conduct appropriate scaffolding learning process by utilizing various graphic organizers and media. While the student teacher was effective in using the scaffolding technique, each theme's improvement path is different. Every meeting is typically used to develop it, and it is acquired in a step-by-step manner.